The Investor Attention Of Financial And Non-Financial Information In North Sumatra In Determining Investment Decision - Silalahi, Alistraja Dison; Silalahi, Cita Ayni Putri; Suginam, Suginam (Politeknik APP Jakarta, 2024)
This study aimed to understand the phenomena experienced by individual investors in North Sumatra in determining investment decisions. This study was qualitative research with a comprehensive description of the experiences, awareness, perceptions, beliefs, memories and feelings experienced by individual investors. Data collection techniques used questionnaires and interviews. The data were analyzed with the assistance of Nvivo 12 Plus software. The results of the study found that the ease of understanding the content and benefits of information became the main concern of the investors. The knowledge possessed by investors in digesting information showed that the available information had provided benefits that showed the compatibility of the quality of information with the quality of individual investors in North Sumatra